Preparo de amostras e análise elementar de produtos farmacêuticos - Garcia, Mariana Ortega (2016)
The medicine manufacture process may cause the final product contamination with metallic residues to the detriment of human healthy. Aiming to regulate the pharmaceutical production and establish standards of final products quality, organizations such as the USP, EMA and ICH established regulations governing maximum exposure to target elements, including some metals that are known to be toxic to human health. Other elements, despite its essentiality in certain concentrations, require exposure control. Regularly a sample to be measured by ICP techniques requires its conversion to a representative solution, usually involving microwave-assisted acid digestion. Once decomposed, the elemental analysis is done using inductively coupled plasma techniques. This study aims to establish a general method of sample preparation and elemental analysis of drug samples (excipients, continuous use drugs, multivitamins, multiminerals and natural products), in order to meet the demands of the pharmaceutical industry. In this sense, sample preparation was based on microwave assisted acid digestion using the following reagents: nitric acid, hydrochloric acid and hydrogen peroxide. The established procedure involves a 41 min heating program with a maximum temperature of 210 oC. The efficiency of digestion was assessed by determination of dissolved organic carbon. Best digestions were reached using 5 ml of inverted aqua regia for 500 mg of sample. The elemental analysis techniques used were ICP OES and ICP-MS. In both cases, analytical calibration curves were built based on the J value, established by USP, which takes into account the permitted daily exposure to the target element, the maximum daily dose of medicament and the sample dilution factor. Both techniques were suitable for metal impurities determination. For ICP OES recoveries were close to 100% for most analytes in all tested samples. For ICP-MS, despite being within the range from 70 to 150% set by USP, recoveries still require further evaluation.